Сauses of Dizziness in Patients with Suspected Stroke - E. V. Shevchenko; G. R. Ramazanov; S. S. Petrikov (Неотложная медицинская помощь, 2018)
Background Acute dizziness may be the only symptom of stroke. Prevalence of this disease among patients with isolated dizziness differs significantly and depends on study design, inclusion criteria and diagnostic methods. In available investigations, we did not find any prospective studies where magnetic resonance imaging, positional maneuvers, and Halmagyi-Curthoys test had been used to clarify a pattern of diseases with isolated acute dizziness and suspected stroke.Aim of study To clarify the pattern of the causes of dizziness in patients with suspected acute stroke.Material and methods We examined 160 patients admitted to N.V. Sklifosovsky Research Institute for Emergency Medicine with suspected stroke and single or underlying complaint of dizziness. All patients were examined with assessment of neurological status, Dix-Hollpike and Pagnini-McClure maneuvers, HalmagyiCurthoys test, triplex scans of brachiocephalic arteries, transthoracic echocardiography, computed tomography (CT) and magnetic resonance imaging (MRI) of the brain with magnetic field strength 1.5 T. MRI of the brain was performed in patients without evidence of stroke by CT and in patients with stroke of undetermined etiology according to the TOAST classification.Results In 16 patients (10%), the cause of dizziness was a disease of the brain: ischemic stroke (n=14 (88%)), hemorrhage (n=1 (6%)), transient ischemic attack (TIA) of posterior circulation (n=1 (6%)). In 70.6% patients (n=113), the dizziness was associated with peripheral vestibulopathy: benign paroxysmal positional vertigo (n=85 (75%)), vestibular neuritis (n=19 (17%)), Meniere’s disease (n=7 (6%)), labyrinthitis (n=2 (1,3%)). In 6.9% patients (n=11), the cause of dizziness was hypertensive encephalopathy, 1.9% of patients (n=3) had heart rhythm disturbance, 9.4% of patients (n=15) had psychogenic dizziness, 0.6% of patients (n=1) had demyelinating disease, and 0.6% of patients (n=1) had hemic hypoxia associated with iron deficiency anemia.Conclusion In 70.6% patients with acute dizziness, admitted to hospital with a suspected stroke, peripheral vestibulopathy was revealed. Only 10% of patients had a stroke as a cause of dizziness.